Inpatient groupwork - Jefford, Adam; Pharwaha, Bhupinderjit Kaur; Grandison, Alistair (Groupwork, 2012)
This paper introduces a model of inpatient groupwork, where the groupworker acts as consultant to the group facilitators. Based loosely on Yalom’s model of inpatient groupwork, weekly sessions are run by two or three staff members. Supervision to the group facilitators is provided fortnightly by the groupwork consultant. This model enables several staff to develop the competencies required to facilitate groupwork in inpatient settings. It contrasts with the more common practice, where groupwork expertise is provided by external specialist practitioners, coming into the wards to conduct sessions. The authors provide some illustrative material from the group sessions. Additional material is provided from supervision sessions, which aim to help staff understand more about the group process and dynamics. In addition to involving more staff in groupwork, the model is also a highly efficient use of the Associate Specialist’s time.